94.9k views
5 votes
PLEASE HELP ME WITH THIS !!!

PLEASE HELP ME WITH THIS !!!-example-1
User Spoike
by
5.5k points

1 Answer

5 votes

9514 1404 393

Answer:

(x -2)^2/16 +(y +2)^2/4 = 1

Explanation:

The equation of an ellipse is ...

((x -h)/a)^2 +((y -k)/b)^2 = 1

where (h, k) is the center, and 'a' and 'b' are the semi-axes in the x- and y-directions respectively.

Here, we have (h, k) = (2, -2), and a=6-2 = 4, b = 0-(-2) = 2. Then the equation is ...

((x -2)/4)^2 +((y +2)/2)^2 = 1

More conventionally, the denominators are multiplied out, so this is ...

(x -2)^2/16 +(y +2)^2/4 = 1

PLEASE HELP ME WITH THIS !!!-example-1
User Brandon Cordell
by
5.0k points